Systematic Literature Review of the Epidemiology of Nongenetic Forms of Hypogonadism in Adult Males. (22nd July 2014) - Zarotsky, Victoria; Huang, Ming-Yi; Carman, Wendy; Morgentaler, Abraham; Singhal, Puneet K.; Coffin, Donna; Jones, T. Hugh
Abstract : This study summarizes the literature on the prevalence, incidence, and proportion of patients receiving treatment for male hypogonadism and a systematic literature search was performed for articles published in the last 20 years. Of the 97 studies identified, 96 examined the prevalence, 2 examined the incidence, and 4 examined the proportion of males with hypogonadism patients receiving treatment. Based on studies conducted in Europe and USA, the prevalence of hypogonadism in the general population ranged from 2.1% to 12.8% of middle-aged to older men, with an estimated incidence of 12 new cases per 1, 000 person-years. Prevalence was higher among patients with comorbid conditions, such as type 2 diabetes mellitus and obesity. Approximately 10–12% of men with hypogonadism were receiving testosterone treatment. This literature review suggests that there is potentially a significant burden of hypogonadism in the general population. Burden seems to increase with age and in the presence of certain disease conditions. Data suggests that many hypogonadal men who may benefit from testosterone replacement are not receiving treatment. This may be the result of underdiagnosis of the disease, lack of awareness by patients or physicians, irregularities surrounding the diagnostic criteria, and deficiency of long-term safety studies.